Exploring Libyan EFL Teachers' Views towards Using Artificial Intelligence Tools in Teaching English Language Translation: A Study at the Department of Translation at the Faculty of Languages within the University of Benghazi (مجلة الفاروق للعلوم, 2026)
It is important to understand teachers' attitudes toward the integration of AI tools in EFL contexts (Almashrgy & Alburki, 2024). This study examined the attitudes of Libyan EFL teachers at the Department of Translation at the Faculty of Languages regarding the integration of Artificial Intelligence in their teaching practices. It aimed to identify both the benefits and challenges of implementing AI in English language teaching. A total of 23 Libyan teachers participated in the research. Employing mixed research methods, presented in a questionnaire consisted of closed-ended questions analyzed using SPSS and open-ended questions analyzed through content analysis, findings of this study revealed that, despite some concerns, most participants believed AI help autonomous learning, increases students' engagement, and improves teachers' administrative tasks. The study emphasized the needs for developing strategies that include training and ethical guidelines to maximize benefits while addressing challenges of AI in language teaching.